Coronary haemodynamic effects of short-term intravenous administration of gallopamil in patients with stable exertional angina. Issue 3 (March 1987) - De Servi, S; Ferrario, M; Ghio, S; Mussini, A; Angoli, L; Bramucci, E; Bartoli, A; Poma, E; Rondanelli, R; Specchia, G
Abstract : The effects of short term intravenous administration of gallopamil on coronary haemodynamic variables were studied in 10 patients with stable exertional angina and angiographically confirmed coronary artery disease that affected the proximal portion of the left anterior descending artery. Blood flow in the great cardiac vein was measured by a thermodilution technique, both at rest and during ischaemia induced by atrial pacing, before and after intravenous administration of gallopamil (0.02 mg/kg as a bolus dose given over three minutes, followed by an infusion of 0.0005 mg/kg/min). Gallopamil significantly prolonged the mean (SD) duration of pacing that was tolerated (11 (2.6) vs 14.8 (2.4] min, significantly increased the mean (SD) peak heart rate attained during pacing (142 (15) vs 158 (11) beats/min), and reduced mean (SD) arterial pressure (133 (17) vs 116 (17) mm Hg). There were no changes in mean (SD) blood flow in the great cardiac vein (134.1 (57) vs 112.9 (38) ml/min, mean (SD) anterior regional coronary resistance (1.18 (0.6) vs 1.15 (0.5) mm Hg/ml/min), and mean (SD) anterior regional myocardial oxygen consumption (16.6 (6) vs 13.7 (4) ml/min). These data confirm that gallopamil is an effective antianginal agent and suggest that a reduction of myocardial oxygen demand is the predominant mechanism by which the drug exerts its beneficial effects.